Peronosporales fungi found on plants of open ground in Botanical Garden of Odessa National Mechnikov University (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The paper contains information on false powdery mildew and white rust fungi (order Peronosporales) that were collected on plants of open ground in Botanical Garden of І.І. Mechnikov Odessa National University. As a result 15 species of Peronosporales were found to parasitize 15 species of plants belonging to 15 genera and 10 families. Most of species belongs to the genus Peronospora (12 species), genera Albugo and Plasmopara contained 2 and 1 species respectively.
Keywords: fungi, Peronosporales, host plants, botanical garden.